2011
DOI: 10.1089/ten.tea.2010.0371
|View full text |Cite
|
Sign up to set email alerts
|

Characterization ofIn VitroEndothelial Linings Grown Within Microfluidic Channels

Abstract: In vivo, endothelial cells grow on the inner surface of blood vessels and are shaped to conform to the vessel's geometry. In the smallest vessels this shape entails substantial bending within each cell. Microfabricated channels can replicate these small-scale geometries, but endothelial cells grown within them have not been fully characterized. In particular, the presence of focal adhesions and adherens junctions in endothelial cells grown in microchannels with corners has not been confirmed. We have fabricate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 44 publications
5
55
0
Order By: Relevance
“…This work demonstrated that the 3D scaffold architecture in the organ-on-a-chip platform allows for cellular interactions that promote 3D capillary morphogenesis through vascular cells. The presence of shear stress was also shown to be responsible for the formation of endothelial vessel linings [38]. Such mechanical stimuli associated with physiological organ motion provide physical cues enabling specific function beyond static tissue culture [27].…”
Section: Fundamental Strategies To Maximize the Efficiency And Predicmentioning
confidence: 99%
“…This work demonstrated that the 3D scaffold architecture in the organ-on-a-chip platform allows for cellular interactions that promote 3D capillary morphogenesis through vascular cells. The presence of shear stress was also shown to be responsible for the formation of endothelial vessel linings [38]. Such mechanical stimuli associated with physiological organ motion provide physical cues enabling specific function beyond static tissue culture [27].…”
Section: Fundamental Strategies To Maximize the Efficiency And Predicmentioning
confidence: 99%
“…Specifically, they are designed to actively influence protein adsorption (the first step of the FBR) and tissue interactions by controlling parameters such as material structure (on a micro/nano level), porosity, drug loading, and surface chemistry (Brodbeck et al, 2002; Bryers et al, 2012; Healy et al, 1996; Lan et al, 2005; Puleo and Nanci, 1999; Ratner, 2002, 2001; Roach et al, 2007; Shin et al, 2003). Commonly, biomimetic materials modify functional groups on the surface of a material or coat the material with ECM molecules (Brodbeck et al, 2002; Chen et al, 2013; Esch et al, 2011; Healy et al, 1996; Lan et al, 2005; Puleo and Nanci, 1999; Roach et al, 2007; Shin et al, 2003). Another thrust of engineering biomimetic materials is to create topographies that either elicit specific biological responses (such as microchannels) or mimic the structure of the ECM (Boudriot et al, 2006; Esch et al, 2011; Roach et al, 2007; Stevens and George, 2005).…”
Section: Biomaterialsmentioning
confidence: 99%
“…Commonly, biomimetic materials modify functional groups on the surface of a material or coat the material with ECM molecules (Brodbeck et al, 2002; Chen et al, 2013; Esch et al, 2011; Healy et al, 1996; Lan et al, 2005; Puleo and Nanci, 1999; Roach et al, 2007; Shin et al, 2003). Another thrust of engineering biomimetic materials is to create topographies that either elicit specific biological responses (such as microchannels) or mimic the structure of the ECM (Boudriot et al, 2006; Esch et al, 2011; Roach et al, 2007; Stevens and George, 2005). …”
Section: Biomaterialsmentioning
confidence: 99%
“…188 Using microuidic channels, it has also been determined that endothelial cells require a minimum initial shear stress in vitro to enable their growth and development to conuent layers that express VE-cadherin, a standard marker for adherence junctions. 189 While polydimethylsiloxane (PDMS) is the most popular material for microuidic systems and carries many advantages, the material properties of the PDMS surface are not ideal. 190 There are concerns that the adsorption of compounds from the medium may interfere with an accurate experimental outcome.…”
Section: Microuidicsmentioning
confidence: 99%